Żyły powierzchowne przedniej okolicy łokciowej u dzieci wiejskich - Gościcka, Danuta; Flisiński, Piotr (Polskie Towarzystwo Antropologiczne, 1992)
Venous configurations of the anterior cubital region were examined on the sample of 203 country children. The occurence of vessel connections of Y -type was found in 91,9%. The variant had 10 modificatins (a-j). Modification of j-type which was observed in boys was the most ramified one. The relation between the kind of the work and the kind of the vessel configuration has been suggested.
Venous configurations of the anterior cubital region